Pengaruh EPS, DER, Kebijakan Deviden, dan Resiko Sistematis terhadap Harga Saham Perusahaan yang Terdaftar di BEI (Studi Pada perusahaan yang masuk dalam Indeks LQ45 di Bursa Efek Indonesia periode 2009-2011) - Paramitha Idi Putri; Djuma hir (Jurnal Ilmiah Mahasiswa FEB, 2012)
Stock prices is an indicator of the value of the company and is a reflection of the relevant information and reflect changes in investor interest in the stock price. This study was to analyze the influence of the effect of Earning Per Share (EPS), Debt Equity Ratio (DER), Dividend Policy, and Systematic Risks to the stock price on the companies included in the Index of Stock Exchange LQ45 in Indonesia of 2009-2011 and which variables were most dominant. Sample selection procedure using saturated sample. The total sample in this study are 20 companies listed in the LQ45 index of Indonesian Stock Exchange (IDX) with the research period of  2009 until 2011 and meet  the criteria established. The analysis technique used is multiple linear regression analysis with a significance level of 5%. The results of this study indicate that the Earning Per Share (EPS) and Equity Ratio (DER) have a significant effect on stock prices, while the Dividend Policy, and Systematic Risk have no significant effect on the stock price and the dominant variables that affect the stock price is variable Earning Per Share (EPS ). Keywords: EPS, DER, Dividend Policy, Systematik Risk, Stock Price